IMPROVING CRITICAL THINKINGABILITY THROUGH GUIDED DISCOVERY METHODS ASSISTED BY CABRI 3D SOFTWARE - Ismail Hanif Batubara; Indah Purnama Sari (CERED Indonesia Institute, 2021)
This research proves that the use of knowledge of software programs such as Cabri 3D improves college students' Critical Thinking competencies compared to those with the software program's help. This evidence is accomplished to reach the development of college students' numerical thinking capacities instructed to use guided disclosure gaining knowledge of strategies assisted with the aid of using Cabri 3D with the guided discovery gaining knowledge of approach without a Computer program. This lesson experimental research takes a look at a populace of 122 people. Randomly instructions are decided on from the to be had guides divided into pattern instructions. The first experimental magnificence changed into given remedy with the aid of using Guided Discovery gaining knowledge of Method assisted with the support of using an Cabri 3D software program, at the same time as some other degree changed into given remedy with the aid of using guided discovery gaining knowledge of approach without Cabri 3D software program. The tool used on this take a look at changed into a check. Then the check effects are examined through the use of the t-check with the assist of SPSS. The check standards are rejected H0 if the table of t is smaller than the t count. Effects confirmed rely on changed into 2,785 simultaneously as the t desk changed into 2,000. The college students taught with the aid of using the guided discovery gaining knowledge of approach assisted with using Cabri 3D (First experiment) are better than without software.